2008
DOI: 10.1534/genetics.108.092718
|View full text |Cite
|
Sign up to set email alerts
|

The Different Sources of Variation in Inbreeding Depression, Heterosis and Outbreeding Depression in a Metapopulation ofPhysa acuta

Abstract: Understanding how parental distance affects offspring fitness, i.e., the effects of inbreeding and outbreeding in natural populations, is a major goal in evolutionary biology. While inbreeding is often associated with fitness reduction (inbreeding depression), interpopulation outcrossing may have either positive (heterosis) or negative (outbreeding depression) effects. Within a metapopulation, all phenomena may occur with various intensities depending on the focal population (especially its effective size) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
156
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(177 citation statements)
references
References 97 publications
17
156
2
1
Order By: Relevance
“…Within-and among-population impact of genetic erosion E Luquet et al First, the expression of fixed deleterious alleles can be specific to a life stage or an environment (Ouborg et al, 2010). Especially in species exhibiting complex life cycle like amphibians, the gene pools expressed during larval and adult stages, in aquatic and terrestrial habitats, respectively, can have different fixation loads and therefore different detrimental effects (Husband and Schemske, 1996;Koelewijn et al, 1999;Escobar et al, 2008).…”
Section: Within-and Among-population Impact Of Genetic Erosion E Luqumentioning
confidence: 99%
See 1 more Smart Citation
“…Within-and among-population impact of genetic erosion E Luquet et al First, the expression of fixed deleterious alleles can be specific to a life stage or an environment (Ouborg et al, 2010). Especially in species exhibiting complex life cycle like amphibians, the gene pools expressed during larval and adult stages, in aquatic and terrestrial habitats, respectively, can have different fixation loads and therefore different detrimental effects (Husband and Schemske, 1996;Koelewijn et al, 1999;Escobar et al, 2008).…”
Section: Within-and Among-population Impact Of Genetic Erosion E Luqumentioning
confidence: 99%
“…Several environmental factors could be responsible to these variations among populations, but determining these factors was beyond the scope of this study. A challenging experiment would be to compare in controlled conditions the detrimental effects of fixation loads at different life stages from embryos to adults on the same cohorts (see Escobar et al, 2008).…”
Section: Within-and Among-population Impact Of Genetic Erosion E Luqumentioning
confidence: 99%
“…Freshwater snails of the Basommatophoran group offer excellent biological models to address these issues (Städler and Jarne, 1997;Charbonnel et al, 2002c;Chapuis et al, 2007;Escobar et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies using neutral genetic markers have also concluded that the population genetic structure at short spatial scale is affected by habitat characteristics (hydrological permanence or habitat openness; for example, Charbonnel et al, 2002c;Trouvé et al, 2003;Bousset et al, 2004). For example, less variation is maintained in closed (for example, ponds) than in open (for example, rivers) habitats (Bousset et al, 2004;Escobar et al, 2008). However, two studies only have compared neutral and phenotypic variation, the first in the lymnaeid Galba truncatula (Chapuis et al, 2007) and the second in the physid Physa acuta (Escobar et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation